Transfer of Erwinia toletana and Erwinia iniecta to a novel genus Winslowiella gen. nov. as Winslowiella toletana comb. nov. and Winslowiella iniecta comb. nov. and description of Winslowiella arboricola sp. nov., isolated from bleeding cankers on broadleaf hosts - Brady, Carrie; Kaur, Sundeep; Crampton, Bridget; Maddock, Daniel; Arnold, Dawn; Denman, Sandra (Frontiers in Microbiology, 2022)
Following a screening campaign of bleeding cankers of broadleaf hosts in Great Britain, numerous bacterial strains were isolated, identified by 16S rRNA and protein-coding gene sequencing and ultimately classified. During the course of the study, several Gram-negative, facultatively anaerobic strains were isolated from bleeding Platanus x acerifolia (London plane) and Tilia x europaea (common lime) cankers that could not be assigned to an existing species. Partial 16S rRNA gene sequencing placed these strains in the genus Erwinia, as a close phylogenetic relative of Erwinia toletana. In an effort to determine the taxonomic position of the strains, a polyphasic approach was followed including genotypic, genomic, phenotypic, and chemotaxonomic assays. Multilocus sequence analysis based on four protein-coding genes (gyrB, rpoB, infB, and atpD) confirmed the phylogenetic position of the strains as a novel taxon of subgroup 3 of the genus Erwinia, along with E. toletana and E. iniecta, and furthermore, provided support for their reclassification in a novel genus. Whole genome comparisons allowed the delimitation of the novel species and also supported the proposed transfer of subgroup 3 species to a novel genus in the Erwiniaeae. Phenotypically the novel species could be differentiated from E. toletana and E. iniecta, and the novel genus could be differentiated from the closely related genera Erwinia and Mixta. Therefore, we propose (1) the reclassification of E. toletana and E. iniecta in a novel genus, Winslowiella gen. nov., as Winslowiella toletana comb. nov. and Winslowiella iniecta comb. nov., with W. toletana comb. nov. as the type species (type strain A37T = CFBP 6631T = ATCC 700880T = CECT 5263T), and (2) classification of the novel strains as Winslowiella arboricola sp. nov. (type strain BAC 15a-03bT = LMG 32576T = NCPPB 4696T).